Analysis of the Research and Experimental Study Results in the Self-Driving Clod-Crusher of the Potato Digger - Tarverdyan, A. P.; Yesoyan, A. M.; Altunyan, A. V.; Hayrapetyan, H. H. (ՀԱԱՀ հիմնադրամ)
Laboratory experiments on the self-driving rotary clod-crusher in the potato digger has been implemented which is aimed at the specification of kinematic and dynamic parameters resulted from the theoretical researches. During the experiments a torque measuring resistance strain gage of TRA-50K series, Zet-210 analog-to-digital converter, appropriate booster (Zet-410) and recording equipment have been used. Three finger types of the recommended clod-crusher have been experimented: cylindrical, cylindrical with hemispheric facade and conical. The experiments indicate that the theoretical research results accurately address the principle of the problem and they can serve as a background for the design and preparation of the clod-crusher.
Keywords: Agricultural Engineering